Experiences of Online Teaching Learning of Students Enrolled in the Universities of Lahore during the Multi Lockdown due to Covid-19 - Fazil, Hina; Haddayat Ali, Hina; Ahmad, Bilal (Pakistan Languages and Humanities Review, 2022)
Universities along with all other educational institutions were being suspended in almost all countries since April 2020, and in the second phase of COVID lockdown the entire education system had shifted on on-line mode from traditional teaching. The study aimed to describe the experiences of students during on-line classes. The research design was quantitative. A close ended questionnaire was used for research reliable at alpha=.89. The researchers have selected 6 universities and collected data from 262 students from Lahore randomly. Study reveals that there is no significance difference (t=0.544, df=260, sig=0.587) in the experiences of students based on their gender. All male and female students have same opinions. Since the r=.514, Sig=.000, N=262 indicate a significance positive correlation between Novitiate experiences of on-line class and good experiences. The participants from University of the Punjab, UMT, UET and other have same views (F=1.111, df=261and Sig=0.345). We recommended that Institutions that offer on-line courses or programs should make an effort to facilitate the faculties of higher education institutions about the effective use of technological tools and gadgets for on-line and blended learning for students to achieve their learning outcomes.